2019
DOI: 10.3390/aerospace6020016
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Heat Transfer Characteristics in a Highly Thermally Loaded Film Cooling Configuration with TBC in Syngas

Abstract: Future power equipment tends to take hydrogen or middle/low heat-value syngas as fuel for low emission. The heat transfer of a film-cooled turbine blade shall be influenced more by radiation. Its characteristic of conjugate heat transfer is studied experimentally and numerically in the paper by considering radiation heat transfer, multicomposition gas, and thermal barrier coating (TBC). The Weighted Sum of Gray Gases Spectral Model and the Discrete Transfer Model are utilized to solve the radiative heat transf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…On an average, a temperature rise of 94 K to 54 K is observed on the metallic plate when gas radiation effects were considered. Singh et al [27] and Ren et al [45] also reported an increment in the surface temperature while considering gas radiation. The contours of TBC effectiveness for the forward and reverse injection case without considering and with consideration of the gas radiations effects confirm the reduction in TBC effectiveness as shown in Fig.…”
Section: Effect Of Gas Radiationmentioning
confidence: 93%
“…On an average, a temperature rise of 94 K to 54 K is observed on the metallic plate when gas radiation effects were considered. Singh et al [27] and Ren et al [45] also reported an increment in the surface temperature while considering gas radiation. The contours of TBC effectiveness for the forward and reverse injection case without considering and with consideration of the gas radiations effects confirm the reduction in TBC effectiveness as shown in Fig.…”
Section: Effect Of Gas Radiationmentioning
confidence: 93%